The Effect Of Advertising And Service Quality On Traveloka Online Plane Ticket Purchase Decisions Among The People Of Kupang City - Damaris Y. Koli; Endang Damaris Koli; Alfred G.O. Kase; Jemmy Jonson Sula Dethan (Lembaga Bale Literasi, 2025)
This study examines the influence of advertising and service quality on the purchase decision of Traveloka online flight tickets among the people of Kupang, East Nusa Tenggara, Indonesia. A quantitative approach with a causal design was employed. The population consisted of all Kupang residents who had ever purchased flight tickets through Traveloka, and a sample of 96 respondents was determined using the Rao Purba formula. Data were collected through questionnaires and analyzed using multiple linear regression, t-tests, F-tests, and coefficient of determination. The results show that advertising has a positive and significant partial effect on purchase decisions (t = 2.801, p < 0.05), and service quality also has a positive and significant partial effect (t = 2.693, p < 0.05). Simultaneously, both variables significantly influence purchase decisions (F = 7.270, p < 0.05). However, the adjusted R² value is only 0.117, indicating that advertising and service quality explain just 11.7% of the variance in purchase decisions. Descriptive analysis shows that respondents perceive both advertising and service quality as high, with mean index scores of 87.3 and 82.6 respectively. The study concludes that while advertising and service quality are important determinants, other factors such as price, trust, and word-of-mouth likely play larger roles. Traveloka should maintain its advertising effectiveness and improve responsiveness to customer complaints. Future research should include additional variables to better explain purchase decisions.